fizyka pomocy przekształć wzory
[tex]s = \frac{1}{2} \times a \times {t}^{2} \: (a)[/tex]
[tex]g = \frac{m1 \times m2}{ {r}^{2} } \: (m1)[/tex]
[tex]f = k \times \frac{q1 \times q2}{ {r}^{2} } (r)[/tex]
[tex]f = \frac{m \times {q}^{2} }{2} (m)[/tex]
[tex]v = \frac{s}{t} (t)[/tex]


Odpowiedź :

[tex]s = \frac{1}{2}\cdot a\cdot t^{2} \ \ /\cdot2\\\\a\cdot t^{2} = 2s \ \ /:t^{2}\\\\\underline{a = \frac{2s}{t^{2}}}[/tex]

[tex]g = \frac{m_1\cdot m_2}{r^{2}} \ \ /\cdot r^{2}\\\\m_1\cdot m_2 = g\cdot r^{2} \ \ /:m_2\\\\\underline{m_1 = \frac{g\cdot r^{2}}{m_2}}[/tex]

[tex]F = k\cdot\frac{q_1\cdot q_2}{r^{2}} \ \ /\cdot r^{2}\\\\F\cdot r^{2} = k\cdot q_1\cdot q_2 \ \ /:F\\\\r^{2} = \frac{k\cdot q_1\cdot q_2}{F}\\\\\underline{r = \sqrt{\frac{k\cdot q_1\cdot q_2}{F}}}[/tex]

[tex]f = \frac{m\cdot q^{2}}{2} \ \ /\cdot 2\\\\m\cdot q^{2} = 2f \ \ /:q^{2}\\\\\underline{m = \frac{2f}{q^{2}}}[/tex]

[tex]v = \frac{s}{t} \ \ /\cdot t\\\\v\cdot t = s \ \ /:v\\\\\underline{t = \frac{s}{v}}[/tex]